2013
DOI: 10.1002/oby.20645
|View full text |Cite
|
Sign up to set email alerts
|

CCDC3 is specifically upregulated in omental adipose tissue in subjects with abdominal obesity

Abstract: Objective: The aim of this study was to search for novel markers of visceral adiposity. Methods: Visceral (omental) and subcutaneous adipose tissues were obtained from 43 Japanese men. Microarray analysis using total RNA from visceral and subcutaneous adipose tissues obtained from five men with abdominal obesity and five nonobese men was first conducted. Then the expression pattern of candidate genes identified in the human study in mouse models of adiposity was examined. Results: Among 30,500 genes evaluated,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…Importantly, the present study showed that these genes are also differentially expressed in rhesus WAT. CCDC 3 has been previously shown to be upregulated in omental WAT of obese subjects and exerts adipogenic effects in vitro and in vivo 76,77 . In the present study, CCDC3 was found to be upregulated and differentially methylated at the same intronic region by either WSD or T + WSD treatment, suggesting a diet-specific mechanism of gene regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the present study showed that these genes are also differentially expressed in rhesus WAT. CCDC 3 has been previously shown to be upregulated in omental WAT of obese subjects and exerts adipogenic effects in vitro and in vivo 76,77 . In the present study, CCDC3 was found to be upregulated and differentially methylated at the same intronic region by either WSD or T + WSD treatment, suggesting a diet-specific mechanism of gene regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The CLSTN2 (calsyntenin 2) is associated with obesity in mammals, particularly in the process of increasing the adipocytes in visceral tissues and subcutaneous fat (Ugi et al . ), and its expression was related to metabolic disorders such as glucose metabolism disorder, disorder of the pancreas, diabetes mellitus, non‐insulin‐dependent diabetes mellitus and insulin‐dependent diabetes mellitus (Mas et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…In turn, two SNPs associated with REA in Chr 3 were in the DPYD gene (dihydropyrimidine dehydrogenase) that encodes an enzyme linked to the first step of the thymine and uracil catabolism (Takai et al 1994). The CLSTN2 (calsyntenin 2) is associated with obesity in mammals, particularly in the process of increasing the adipocytes in visceral tissues and subcutaneous fat (Ugi et al 2014), and its expression was related to metabolic disorders such as glucose metabolism disorder, disorder of the pancreas, diabetes mellitus, non-insulin-dependent diabetes mellitus and insulin-dependent diabetes mellitus (Mas et al 2013). Apparently, the FBLN1 and LOC531152 have no direct link with the REA.…”
Section: Discussionmentioning
confidence: 99%
“…CLSTN2 (calsintenin 2) is associated with obesity in mammals, especially in the process of increasing adipocytes in visceral tissues and in subcutaneous fat [56]. Santana et al [57] defined CLSTN2 as a candidate gene associated with ultrasound-derived measurements of the rib-eye area, backfat thickness and rumpfat thickness in Nellore cattle.…”
Section: Potential Candidate Genes For Litter Traits Of Pigmentioning
confidence: 99%